Comparison of creatinine‐based methods for estimating glomerular filtration rate in patients with heart failure - Anna Jonsson; Ida Viklund; Andreas Jonsson; Fredrik Valham; Ellinor Bergdahl; Krister Lindmark; Helena Norberg (ESC Heart Failure, 2020)
Abstract Aims Glomerular filtration rate is an important factor in management of heart failure (HF). Our objective was to validate eight creatinine‐based equations for estimating glomerular filtration rate (eGFR) in an HF population against measured glomerular filtration rate. Methods and results One hundred forty‐six HF patients (mean age 68 ± 13 years, mean left ventricular ejection fraction 45% ± 15) within a single‐centre hospital that underwent 51Cr‐EDTA clearance between 2010 and 2018 were included in this retrospective study. eGFR was estimated by means of Cockcroft–Gault ideal and actual weight, the Modification of Diet in Renal Disease Study (MDRD), simplified MDRD with isotope dilution mass spectroscopy traceable calibration, the Chronic Kidney Disease Epidemiology Collaboration, revised Lund–Malmö, full age spectrum, and the Berlin Initiative Study 1. Mean measured glomerular filtration rate was 42 mL/min/1.73 m2. Pearson's correlation coefficient (r) had the highest precision for MDRD (r = 0.9), followed by revised Lund–Malmö (r = 0.88). All equations except MDRD (mean difference −4.8%) resulted in an overestimation of the renal function. The accuracy was below 75% for all equations except MDRD. Conclusions None of the exclusively creatinine‐based methods was accurate in predicting eGFR in HF patients. Our findings suggest that more accurate methods are needed for determining eGFR in patients with HF.